Environmental factors other than iodine deficiency in the pathogenesis of endemic goiter in the basin of river Ganga and Bay of Bengal, India - Amar K Chandra; Arijit Debnath; Smritiratan Tripathy; Haimanti Goswami; Chiranjit Mondal; Arijit Chakraborty; Elizabeth N Pearce (Wolters Kluwer Medknow Publications, 2016)
Background: In iodine-replete basin of the river Ganga and the Bay of Bengal, we studied iodine nutritional status of school children by goiter prevalence and their urinary iodine (UI), iodine content in edible salt, and the bioavailability of iodine through water and its contribution to iodine nutrition. We also studied consumption pattern of common goitrogenic plants by measuring urinary thiocyanate (USCN), hardness of water (calcium and magnesium salt content) and assessed the effect of concomitant exposure of those environmental factors in goitrogenesis. Methods: 4603 children aged 6-12 years were examined for goiter by palpation, 520 urine samples were analyzed for UI and USCN; iodine content was estimated in 455 household salt and 130 water samples tested both for iodine and hardness. Results: The total goiter rate was 35.9%, median UI was 231 ΅g/l, mean USCN was 0.857 ± 0.48 mg/dl, iodine content in water was 44.7 ± 4.1 ΅g/l, 66.4% of salt samples contained iodine (15 ppm), and water was found to be hard. UI was correlated with both the drinking water iodine content and USCN and the degree of hardness in drinking water was associated with goiter prevalence. Conclusions: The studied population has endemic goitre despite iodine sufficiency. The concomitant exposure of a number of environmental factors, i.e., thiocyanate of cyanogenic plant food, hardness of drinking water, and excess iodine from environmental sources other than iodide salt are likely responsible for the causation and persistence of endemic goiter in the region.